DEVELOPMENT AND INTRODUCTION TYPICAL COMPLEX ECOLOGY-GEOLOGICAL PROGRAM OF RESEARCH THE TERRITORIES OF WAREHOUSES AND BASES OF COMBUSTIBLES-LUBRICANT MATERIALS - DYNIAK, S.; MAKSYMOV, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The ecological situation concerning petrochemical contamination in Ukraine should be esteemed as crisis. The contamination by petroleum concerns first of all underground waters, that is the basic source of drinking water supply. The example of creation of the complex ecology-geologic program is adduced with the purpose of systematisation and organization of the scientifically reasonable and effective activity, which one directional on study both rehabilitation of terrains of warehouses and bases of combustibles - lubricants in places of petrochemical contamination and other concomitant materials.